MaglevMotor: Design and optimisation of a novel hybrid linear actuator for 6 degrees of freedom rail-passive Maglev carrier - Bozkurt, Ahmet Fevzi; Erkan, Kadir (WILEY, 2024)
A novel levitating hybrid linear actuator is proposed for magnetically levitated carrier systems. This hybrid linear actuator, MaglevMotor, is capable to levitate itself under the passive rail and thrusts itself in a single longitudinal direction. The proposed structure aims to reduce complexity by minimising the necessary number of components, resulting in simplified geometry, improved assembly convenience, and decreased manufacturing tolerances. The MaglevMotor is optimised in multi-physics aspect. Optimisation objectives are maximising thrust force, minimising total mass and minimising mechanical deformation of yoke with constraints of a user defined magnetic flux density (B) in yoke and zero power condition for specific air gap value. The authors present pre-optimisation studies, optimisation results and final MaglevMotor designs step by step. By utilising three of the MaglevMotors units, the carrier is able to achieve motion in six degrees of freedom. The carrier's performance targets, including a 0.2 G acceleration, a total mass of less than 10 kg, and a 5 mm levitation air gap, have been both attained and validated through corresponding experiments. A novel levitating hybrid linear actuator is proposed for magnetically levitated carrier systems. This hybrid linear actuator, MaglevMotor, is capable to levitate itself under the passive rail and thrusts itself in a single longitudinal direction. The proposed structure aims to reduce complexity by minimising the necessary number of components, resulting in simplified geometry, improved assembly convenience, and decreased manufacturing cost. The final optimised design, with the optimisation steps, including pre-optimisation studies and the multi objective genetic algorithm results are presented. image
Keywords: hybrid yoke; linear induction motors; magnetic actuators; magnetic levitation; optimisation; SYSTEM; Engineering